Phenotypic and genotypic characteristics of carbapenem-resistant Enterobacteriaceae in a tertiary-level reference hospital in Turkey. Issue 1 (December 2016) - Baran, Irmak; Aksu, Neriman
Abstract Background Enterobacteriaceae are among the most common pathogens that are responsible for serious community-acquired, hospital-acquired, and health-care associated infections. The emergence and spread of carbapenem-resistantEnterobacteriaceae (CRE) have become an increasing concern for healthcare services worldwide. Infections caused by these bacteria have been associated with significant morbidity and mortality and treatment options have been limited. The rapid and accurate detection of carbapenem resistance in these bacteria is important for infection control. The aim of this study was to investigate the phenotypic and genotypic features of CRE strains isolated in a tertiary-level reference hospital in Turkey. Methods A total of 181 CRE strains were included in the study. Antimicrobial susceptibility rates were tested using Vitek 2 system. Modified Hodge test (MHT) was performed using meropenem and ertapenem discs. Metallo-β-lactamase antimicrobial gradient test (E-test MBL strips) were used for evaluation of metallo-β-lactamase production. A multiplex PCR was used for detection of carbapenems resistance genes (IMP, VIM, KPC, NDM-1 and OXA-48). Results The OXA-48 gene was detected in 86 strains, NDM-1 gene in six strains, VIM gene in one strain. IMP and KPC genes were not identified. Three strains produced both OXA-48 and NDM-1 and one strain produced both OXA-48 and VIM. In two patients more than one genus of OXA-48 positive CREs was isolated. Ninety-two of the isolates were multidrug-resistant. One hundred and ten isolates were MHT with meropenem (MEM-MHT) positive and 109 isolates were MHT with ertapenem (ERT-MHT) positive. Nine of the isolates were positive with E-test MBL strips. The sensitivity of MEM-MHT and ERT-MHT for detection of OXA-48 was 70.9 and 70.6 %, respectively. MEM-MHT was found highly discriminative for OXA-48Escherichia coli (p < 0.001). The sensitivity of E-test MBL for NDM-1 was 66.7 %. A statistically significant correlation was observed between OXA-48 gene and MHT positivity and between NDM-1, VIM gene and E-test MBL positivity (p < 0.001). Conclusions OXA-48 gene is spreading rapidly to many different species ofEnterobacteriaceae in the hospital environment. While OXA-48 is still the most common source of carbapenem resistance inEnterobacteriaceae in our country, NDM-1 is increasingly being isolated from patients without a history of foreign contact.